LEGAL EXPLANATION (RESTATEMENT) OF THE CONCEPT OF GOVERNMENT ADMINISTRATIVE ACTIONS ACCORDING TO LAW NO. 30 OF 2014 CONCERNING GOVERNMENT ADMINISTRATION - Muhammad Adiguna Bimasakti (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2022)
Law No. 30 of 2014 concerning Government Administration (UU AP) stipulates two types of Administrative Actions, namely Government Decrees and Government Administrative Actions. In judicial practice in the administrative courts, the term Government Administrative Action is often interpreted differently from the concept of Real Action. This study aims to determine the concept of Government Administrative Action according to Law No. 30 of 2014 concerning Government Administration. The writing method used in this research is normative juridical method using statutory approach and conceptual approach. The results of the study show that the concept of